How do you solve 5x - 4= 2x - 13?

2 Answers

x= -3

Explanation:

Step 1: Subtract 2x from both sides of the equation. Thus, you have

3x-4=-13

Step 2: Add 4 to both sides. You now have

3x= -9

Step 3: Multiply each side by 1/3. Thus, you are left with

x= -3

Mar 6, 2018

x=-3

Explanation:

We know that if we perform the same operation on both sides of the equation, we still get an equality. We start with the equation:

5x-4=2x-13

We now try to isolate the x's. That is, we want to put all the x's on one side:

5x-4-2x=2x-13-2x

Combine like terms:

3x-4=-13

We now add 4 to both sides:

3x-4+4=-13+4

3x=-9

Finally, we divide both sides by 3:

(3x)/3=(-9)/3

x=-3